Safety profile of a special butterbur extract from in migraine prevention with emphasis on the liver - HC Diener; FG Freitag; U Danesch (SAGE Publishing, 2018)
Background: Butterbur supplements are available in the USA and Canada and are commonly used for treating migraines. Petadolex, a special butterbur extract from Petasites hybridus, is a natural herbal product and the only butterbur extract with proven clinical efficacy in migraine prevention. The Complimentary Migraine Guidelines of the AAN mention butterbur as level A recommendation for the prevention of chronic episodic migraine. However, these guidelines have been retired. Methods: We review suspected serious liver cases, pyrrolizidine alkaloids, regulatory issues, preclinical and clinical data of the special butterbur extract Petadolex. Results: The RUCAM (Roussel Uclaf Causality Assessment Method) test found no probable relationship between the butterbur root extract Petadolex® and cases of serious liver injury. Two cases of non-serious reversible liver enzyme elevations were rated as probably related to Petadolex®. The safety is supported by preclinical data in animals as well as in-vitro toxicology experiments. In addition, Petadolexis free of detectable levels of pyrrolizidine alkaloids. Conclusion: There is no evidence that the special butterbur root extract Petadolex poses a substantial risk of liver injury for patients.